Immigration-specific stress and 24-hour movement behaviors among international nurses in Japan: a network and time-series network analysis using wearable device data - Xinyi Chang; Xiuzhu Gu (BMC Nursing)
Abstract Background As a sharp increase in healthcare demand has led to a severe shortage of nurses in aging societies, international nurses become to play a crucial role in supporting healthcare systems. However, they often face immigration-specific stress that may influence their 24-hour movement behaviors, including physical activity, sedentary behavior, and sleep, as key determinants of health. Despite the importance of these behaviors, limited research has examined the complex interrelationships among 24-hour movement behaviors in this population. This study examined the interrelationships among 24-hour movement behaviors of international nurses working in Japanese healthcare organizations using wearable devices and explored the relationship between these behaviors and immigration-specific stress. The findings aim to inform interventions to promote healthier behavioral patterns and enhance patient safety within healthcare organizations. Methods A total of 43 international nurses working in Japanese healthcare organizations participated in this study. They wore a Fitbit Charge 5 device for 4 weeks to record their daily 24-hour movement behaviors. Upon completion of the tracking period, participants completed a questionnaire assessing immigration-specific stress. We employed network analysis to investigate the relationship between immigration-specific stress and 24-hour movement behaviors, and temporal network analysis to explore the internal interactions within 24-hour movement behaviors. Results International nurses exhibited insufficient sleep duration. Network analysis revealed that the ‘Not at home’ feeling (lack of sense of belonging), ‘Occupation’ disadvantages (occupational development inequities) and ‘Novelty’-related challenges (unfamiliarity with workplace norms and tasks) negatively related to sleep duration. ‘Novelty’-related challenges were also negatively related to moderate-to-vigorous physical activity (MVPA). Temporal network analysis further indicated that increased MVPA was beneficial in improving subsequent sleep duration. Conclusion This study highlighted that sleep duration in international nurses may be improved by enhancing their sense of belonging, eliminating occupational development inequities, and coping with novelty-related challenges. Specific measures include developing more inclusive immigration policies, career development opportunities and continuing education to support international nurses. Additionally, physical activity programs, along with support for novelty-related challenges, can promote appropriate levels of MVPA and further improve sleep duration. Trial registration Not applicable.